Phân tích đa thức sau thành nhân tử:
(a2 + b2 + ab) 2 - a2b2 - b2c2 - c2a2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1: Ta có: \(a^2+b^2+c^2\)
\(=\left(a+b+c\right)^2-2\cdot\left(ab+bc+ca\right)\)
\(=5^2-2\cdot174=-323\)
b: \(xy\left(x+y\right)-yz\left(y+z\right)+xz\left(x-z\right)\)
\(=x^2y+xy^2-y^2z-yz^2+x^2z-xz^2\)
\(=x^2y-yz^2+xy^2-y^2z+x^2z-xz^2\)
\(=y\left(x-z\right)\left(x+z\right)+y^2\left(x-z\right)+xz\left(x-z\right)\)
\(=\left(x-z\right)\left(xy+yz+y^2+xz\right)\)
\(=\left(x-z\right)\left(x+y\right)\left(x+z\right)\)
a) \(a^2+ab-7a-7b=a\left(a+b\right)-7\left(a+b\right)=\left(a+b\right)\left(a-7\right)\)
b) \(5ab+4c+20b+ac=5b\left(a+4\right)+c\left(a+4\right)=\left(a+4\right)\left(5b+c\right)\)
c) \(a^2+6a-b^2+9=\left(a+3\right)^2-b^2=\left(a+b-b\right)\left(a+3+b\right)\)
d) \(a^2-16=\left(a-4\right)\left(a+4\right)\)
(a2+b2+ab)2-a2b2-b2c2-c2a2
=a4+b4+a2b2+2.(a2b2+a3b+ab3)-a2b2-b2c2-c2a2
=a4+b4+a2b2+2a2b2+2a3b+2ab3-a2b2-b2c2-c2a2
=a4+b4+2a2b2+2a3b+2ab3-b2c2-c2a2
= (a4+b4+2a2b2)+(2a3b+2ab3)-(c2a2+b2c2)
= (a2+b2)2+2ab(a2+b2)-c2(a2+b2)
= (a2+b2)(a2+b2+2ab-c2)
=(a2+b2)[(a+b)2-c2]
=(a2+b2)(a+b+c)(a+b-c)